Prediction of crack propagation path in pin loaded lugs using boundary element method - Tan, Zhi Hui (Nanyang Technological University, 2020)
Boundary element method was deployed to analyse the stress concentration factor and stress intensity factor of a pin loaded straight lug. The approach was to model the straight lug and cracks in a boundary element method programme called BIE2DS. Effects of varying loading orientation on the pin hole circumference, as well as varying outer-to-inner radius ratio of the lug, were investigated. It was concluded that the highest stress intensity factor was found in the loading direction perpendicular to the lug axis. Stress intensity factor was also found to decrease with increase outer-to-inner radius ratio.